Bio‐Inspired Formal Synthesis of Hirsutellones A–C Featuring an Electrophilic Cyclization Triggered by Remote Lewis Acid‐Activation. Issue 48 (18th October 2013) - Li, Xu‐Wen; Ear, Alexandre; Roger, Lukas; Riache, Nassima; Deville, Alexandre; Nay, Bastien
Abstract A bio‐inspired strategy was used to complete the formal synthesis of the antitubercular hirsutellone B and congeners A and C, through construction of its decahydrofluorene core from a linear polyene strand activated at both ends by a silyl enol ether and an allyl acetate. Our synthesis features a key electrophilic cyclization, starting with the remote activation (by [Yb(OTf)3] or BF3⋅OEt2) of the allyl acetate and stereoselectively affording the C ring. This was followed by an intramolecular Diels–Alder reaction to get the tricyclic core of the natural product. The stereoselective reduction of the resulting ketone towards the formal intermediate was critical to the success of this strategy.